Hubungan Antara Kitab Hukum Kanonik 1983 dan Konsili Vatikan II: Perspektif Teologi Pastoral - Ranubaya, Fransesco Agnes; Reginald, Reginald; Louis, Johannes; Dendri, Dendri; Meo, Yohanes Wilson B. Lena; Endi, Yohanes (Jurnal Masalah Pastoral, 2025)
This study examines the relationship between the 1983 Code of Canon Law and the Second Vatican Council from a pastoral theological perspective. The 1983 Code of Canon Law represents a significant reform in the Catholic Church’s legal structure, shifting from a juridical to a pastoral approach, largely influenced by the theological renewal of the Second Vatican Council. This research aims to analyze the continuity and transformation of canonical norms, particularly in their application within the Church's pastoral life. Using a qualitative method with a textual analysis approach, this study reviews official Church documents, including the 1983 Code of Canon Law and the decrees of the Second Vatican Council, applying hermeneutical and theological reflections. The findings reveal that the 1983 Code of Canon Law integrates key elements of Vatican II’s ecclesiology, emphasizing the communal nature of the Church and the active participation of the laity. Furthermore, the study highlights the pastoral dimension of canonical law, particularly in its flexibility and responsiveness to contemporary pastoral needs. The study concludes that the reforms brought by the 1983 Code of Canon Law reflect a deeper alignment with Vatican II’s vision, reinforcing the Church’s mission in a more inclusive and adaptive manner. These insights provide theological and pastoral implications for Church leaders and scholars in applying canonical norms effectively within pastoral contexts.